Needs for Increased Awareness of Gastrointestinal Manifestations in Patients With Human Inborn Errors of Immunity - Kim, Eun Sil; Kim, Dongsub; Yoon, Yoonsun; Kwon, Yiyoung; Park, Sangwoo; Kim, Jihyun; Ahn, Kang Mo; Ahn, Soomin; Choe, Yon Ho; Kim, Yae-Jean; Kim, Mi Jin (Frontiers in Immunology, 2021)
The gastrointestinal (GI) tract is frequently affected by inborn errors of immunity (IEI), and GI manifestations can be present in IEI patients before a diagnosis is confirmed. We aimed to investigate clinical features, endoscopic and histopathologic findings in IEI patients. This was a retrospective cohort study conducted from 1995 to 2020. Eligible patients were diagnosed with IEI and had GI manifestations that were enough to require endoscopies. IEI was classified according to the International Union of Immunological Societies classification. Of 165 patients with IEI, 55 (33.3%) had GI manifestations, and 19 (11.5%) underwent endoscopy. Among those 19 patients, nine (47.4%) initially presented with GI manifestations. Thirteen patients (68.4%) were male, and the mean age of patients 11.5 ± 7.9 years (range, 0.6 – 26.6) when they were consulted and evaluated with endoscopy. The most common type of IEI with severe GI symptoms was “Disease of immune dysregulation” (31.6%) followed by “Phagocyte defects” (26.3%), according to the International Union of Immunological Societies classification criteria. Patients had variable GI symptoms such as chronic diarrhea (68.4%), hematochezia (36.8%), abdominal pain (31.6%), perianal disease (10.5%), and recurrent oral ulcers (10.5%). During the follow-up period, three patients developed GI tract neoplasms (early gastric carcinoma, mucosa associated lymphoid tissue lymphoma of colon, and colonic tubular adenoma, 15.8%), and 12 patients (63.2%) were diagnosed with inflammatory bowel disease (IBD)-like colitis. Investigating immunodeficiency in patients with atypical GI symptoms can provide an opportunity for correct diagnosis and appropriate disease-specific therapy. Gastroenterologists and immunologists should consider endoscopy when atypical GI manifestations appear in IEI patients to determine if IBD-like colitis or neoplasms including premalignant and malignant lesions have developed. Also, if physicians in various fields are better educated about IEI-specific complications, early diagnosis and disease-specific treatment for IEI will be made possible.